2019
DOI: 10.3389/fpsyt.2019.00140
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Degree Centrality Associated With Cognitive Dysfunctions in Early Bipolar Disorder

Abstract: Delayed diagnosis of bipolar disorder (BD) is common. However, diagnostic validity may be enhanced using reliable neurobiological markers for BD. Degree centrality (DC) is one such potential marker that enables researchers to visualize neuronal network abnormalities in the early stages of some neuropsychiatric disorders. In the present study, we measured resting-state DC abnormalities and cognitive deficits in order to identify early neurobiological markers for BD. We recruited 23 patients with BD who had rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 62 publications
(62 reference statements)
0
18
0
Order By: Relevance
“…DC can reflect the relative importance of a node in a network (Yang et al, 2014), which has been widely used to study neurological and psychiatric disorders. Recently, one study used DC to explore cognitive dysfunction in patients with early bipolar disorder (Deng et al, 2019). Guo et al (2016) revealed DC changes in the right middle frontal, precentral, and postcentral gyri, which fits a network dysfunction model in Alzheimer's disease (AD).…”
Section: Introductionmentioning
confidence: 89%
“…DC can reflect the relative importance of a node in a network (Yang et al, 2014), which has been widely used to study neurological and psychiatric disorders. Recently, one study used DC to explore cognitive dysfunction in patients with early bipolar disorder (Deng et al, 2019). Guo et al (2016) revealed DC changes in the right middle frontal, precentral, and postcentral gyri, which fits a network dysfunction model in Alzheimer's disease (AD).…”
Section: Introductionmentioning
confidence: 89%
“…Indeed, neuroimaging studies have described cerebellar alterations in patients with bipolar disorder [ 24 , 25 , 26 , 27 ] over the last twenty years and researchers have focused on this structure [ 28 , 29 , 30 , 31 , 32 ] in light of the cerebellar connections with cortical areas involved in the pathophysiology of bipolar disorder [ 13 , 28 , 31 , 33 , 34 ] and the cerebellar role in emotion [ 35 , 36 , 37 , 38 , 39 ], social cognition [ 16 , 40 , 41 ] and cognitive functions [ 42 , 43 , 44 , 45 ]. Moreover, it is worth noting that very recently the onset of mood disorders (manic and depressive symptoms) has been demonstrated in the presence of isolated cerebellar lesions and neurodegenerative cerebellar pathologies [ 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, better psychomotor speed was generally considered related to larger gray matter volumes in the bilateral prefrontal lobe, bilaterally hippocampus, and left superior temporal gyrus in normal controls (26). Psychomotor speed was associated with degree centrality abnormalities of the temporal lobe in early BD patients (27). Furthermore, a positive relationship between the inferior temporal surface area and psychomotor speed was reported in BD (28).…”
Section: Discussionmentioning
confidence: 99%